2001
DOI: 10.1080/02791072.2001.10399922
|View full text |Cite
|
Sign up to set email alerts
|

Drug Court Effectiveness: A Review of California Evaluation Reports, 1995–1999

Abstract: Over the past two decades, drug courts have emerged as a viable alternative for addressing drug cases within the criminal justice system. In California, the Drug Court Partnership Program (DCPP) was created in 1998 and has supported and funded the development of drug courts throughout the State. This article reports on a review of California drug court evaluations through January 2000 conducted as part of an evaluation of the California DCPP. A total of 23 evaluations were collected. Seventeen were reviewed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Program evaluations, utilizing aggregate level data on DTC participants and non-participants at the county level in a variety of jurisdictions, indicate that drug court participation is associated with reduced recidivism and drug use among substance-involved offenders. (Goldkamp and Weiland 1993; Johnson and Latessa 1997; Granfield, Eby et al 1998; Belenko 2001; Brewster 2001; Guydish, Wolfe et al 2001; Listwan, Shaffer et al 2001; Fielding, Tye et al 2002; Carey and Marchand 2005; Marchand, Waller et al 2006) Though encouraging, such aggregate level data fail to take into account a number of critical factors such as selection bias and potentially confounding or modifying factors (e.g. substance use history, prior treatment contacts, criminal justice history, socioeconomic factors, social support, type of treatment received, and other conditions of supervision in drug treatment court) leading to the reductions in recidivism and substance use for DTC participants.…”
Section: Introductionmentioning
confidence: 99%
“…Program evaluations, utilizing aggregate level data on DTC participants and non-participants at the county level in a variety of jurisdictions, indicate that drug court participation is associated with reduced recidivism and drug use among substance-involved offenders. (Goldkamp and Weiland 1993; Johnson and Latessa 1997; Granfield, Eby et al 1998; Belenko 2001; Brewster 2001; Guydish, Wolfe et al 2001; Listwan, Shaffer et al 2001; Fielding, Tye et al 2002; Carey and Marchand 2005; Marchand, Waller et al 2006) Though encouraging, such aggregate level data fail to take into account a number of critical factors such as selection bias and potentially confounding or modifying factors (e.g. substance use history, prior treatment contacts, criminal justice history, socioeconomic factors, social support, type of treatment received, and other conditions of supervision in drug treatment court) leading to the reductions in recidivism and substance use for DTC participants.…”
Section: Introductionmentioning
confidence: 99%
“…A review of California drug courts in particular found that drug court participants' rearrest rates were reduced by 11% to 14%, with the largest reduction in rearrest rates found among individuals graduating from their treatment programs. 15 Research has also been conducted to determine the economic impact of drug courts in the United States and internationally. 16– 18 Yet many methodological and analytical concerns have been raised in the evaluation of drug courts given the selectivity of participants and other concerns, 19 although comprehensive economic analyses are available in the peer-reviewed literature that display reliable cost savings for drug courts.…”
mentioning
confidence: 99%
“…Many counties and states now operate adult and/or juvenile programs. Early evaluations suggest that these programs are effective (Guydish, Wolfe, Tajima, & Woods, 2001;Hicks, 1999;Peters & Murrin, 2000), but we were able to find only one published study on costs and economic benefits (Logan et al, 2004). Criminal justice agencies would certainly appreciate rigorous and standardized information on the costs and benefits of these programs before allocating additional resources.…”
Section: Perform More Economic Evaluations Of Drug Courtsmentioning
confidence: 91%